2015
DOI: 10.1002/2015gl066031
|View full text |Cite
|
Sign up to set email alerts
|

Reconstructing the timescale of a catastrophic fan‐forming event on Earth using a Mars model

Abstract: The calculation of formation timescales of alluvial fans and deltas on Mars is important as it has direct implications for understanding the planet's hydrologic history. The robustness of sediment transport models is not in doubt but validation of the broad approach using a terrestrial example of similar scale and likely origin, where hydraulic parameters and timescales are known, is useful. Using a catastrophically formed terrestrial fan, where abundant sedimentological information is available, we find that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…de Villiers et al (2013) tested the method directly for experimental crater lake deltas and Marra et al (2014) showed it was additionally applicable to erosive experimental systems, and was further supported by a uniquely wellconstrained erosional valley case on Mars: the Aram Chaos side valley to Ares Valles (Roda et al, 2014). More recently, the abovementioned model used was applied to reconstruct the timescale of formation of the several martian deltas (Kleinhans, 2005;Kleinhans et al, 2010) and has already been validated on Earth by Duller et al (2015), who applied it to reconstruct the timescales of the 1918 catastrophically formed fan in southern Iceland (Duller et al, 2008(Duller et al, , 2014. The real known duration of this event was 6-10 h, and the timescale predicted by their modeling is between 2 and 17 h. Furthermore, to strengthen their test, they modeled several hypothetical martian scenarios applied on the Iceland fan to illustrate potential limitations of using the final topography to estimate flow dimensions and using a typical value of grain size distribution recorded from Mars missions (as we did in this work).…”
Section: Model Validationmentioning
confidence: 99%
See 1 more Smart Citation
“…de Villiers et al (2013) tested the method directly for experimental crater lake deltas and Marra et al (2014) showed it was additionally applicable to erosive experimental systems, and was further supported by a uniquely wellconstrained erosional valley case on Mars: the Aram Chaos side valley to Ares Valles (Roda et al, 2014). More recently, the abovementioned model used was applied to reconstruct the timescale of formation of the several martian deltas (Kleinhans, 2005;Kleinhans et al, 2010) and has already been validated on Earth by Duller et al (2015), who applied it to reconstruct the timescales of the 1918 catastrophically formed fan in southern Iceland (Duller et al, 2008(Duller et al, , 2014. The real known duration of this event was 6-10 h, and the timescale predicted by their modeling is between 2 and 17 h. Furthermore, to strengthen their test, they modeled several hypothetical martian scenarios applied on the Iceland fan to illustrate potential limitations of using the final topography to estimate flow dimensions and using a typical value of grain size distribution recorded from Mars missions (as we did in this work).…”
Section: Model Validationmentioning
confidence: 99%
“…While flow and sediment transport predictors undoubtedly simplify reality, the timescales of morphology development are rather well constrained by this methodology. We use these predictors to estimate the duration of the Jezero fluvial system, and we further test it on well-constrained terrestrial (Holocene) cases, including the Wax Lake Delta (WLD) and Lake Constance, to corroborate general validity [previously assessed by Duller et al (2015)]. To obtain a range of possible predictions, we simulated a number of conditions for the most uncertain and sensitive variables (i.e., grain size and channel dimensions).…”
Section: General Approachmentioning
confidence: 99%
“…The best example of cyclic steps in a modern submarine setting are from the subaqueous slope of the sand‐rich glacifluvial Squamish River delta in western Canada, where bedform morphodynamics, flow triggers and the resulting stratigraphy have been studied in detail from direct observations (Hughes Clarke, 2016; Stacey & Hill, 2016; Hizzett et al ., 2018; Hage et al ., 2018, 2019; Stacey et al ., 2019; Vendettouli et al ., 2019). Deposits of antidunes and chutes‐and‐pools are known from modern jökulhlaup deposits in Alaska and Iceland, where the depositional record can be compared with direct observations and estimations of the flood discharge (Burke et al ., 2008, 2010a,b; Duller et al ., 2008, 2015).…”
Section: The Depositional Record Of Glacigenic Upper‐flow‐regime Bedformsmentioning
confidence: 99%
“…Based on the observed bedforms (Table 1B) and compared to sediments of alluvial fans formed under conditions of rapid sedimentation and high discharges (cf. Duller et al, 2015), conditions prevailing during Qt2 through Qt4 were of larger sediment supply than Holocene to present-day conditions, along with active fan deposition. Thicknesses of tens of meters of sediment were deposited at locations in the middle and distal portions of the fans (Figs.…”
Section: Evolution Of Depositional Events In the Recordmentioning
confidence: 99%